Concurrent functional endoscopic sinus surgery and septorhinoplasty: using evidence to make clinical decisions. Issue 6 (7th January 2013) - Patel, Zara M.; Setzen, Michael; Sclafani, Anthony P.; Del Gaudio, John M.
<x xml:space="preserve">Abstract</x> Background Concurrent septorhinoplasty (SRP) and functional endoscopic sinus surgery (FESS) has been a controversial topic in the literature over the last decade. Warnings and admonitions about the risks of performing these procedures together in a single surgery are both published and voiced at national meetings. Although pros and cons have been discussed in the literature, there have been no guidelines published based solely on a review of the level of evidence. Methods A systematic review of the literature was performed and the Clinical Practice Guideline Manual, Conference on Guideline Standardization (COGS), and the Appraisal of Guidelines and Research Evaluation (AGREE) instrument recommendations were followed. Study inclusion criteria were an adult population >18 years old, description or implication of study design available, concurrent FESS and SRP performed without additional procedures, and report of complications included in the study. Results We identified and evaluated the literature meeting those criteria: 11 retrospective studies. The literature was reviewed for both quality of research design as well as benefit and harm of the proposed interventions. Conclusion If a patient is in need of FESS and SRP, either for functional or cosmetic reasons, and is found on the risk matrix to either have low or moderate risk, that patient is a good candidate for a concurrent procedure. If the patient is found to have higher risk, it is not an absolute contraindication, but the surgeon must use best clinical judgment when deciding to move forward and must counsel the patient preoperatively about possible increased risks.